Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 11847 species occurrences available in GBIF matching the query: { "or" : [ "TaxonKey is Hyla euphorbiacea Günther, 1858", "TaxonKey is Exerodonta sumichrasti Brocchi, 1879", "TaxonKey is Pachymedusa dacnicolor (Cope, 1864)", "TaxonKey is Megastomatohyla nubicola (Duellman, 1964)", "TaxonKey is Megastomatohyla pellita (Duellman, 1968)", "TaxonKey is Megastomatohyla mixomaculata (Taylor, 1950)", "TaxonKey is Plectrohyla ameibothalame (Canseco-Márquez, Mendelson & Gutiérrez-Mayén, 2002)", "TaxonKey is Plectrohyla arborescandens (Taylor, 1939)", "TaxonKey is Plectrohyla acanthodes Duellman & Campbell, 1992", "TaxonKey is Hyla arboricola Taylor, 1941", "TaxonKey is Hyla eximia Baird, 1854", "TaxonKey is Plectrohyla bistincta (Cope, 1877)", "TaxonKey is Plectrohyla calthula (Ustach, Mendelson, McDiarmid & Campbell, 2000)", "TaxonKey is Exerodonta xera (Mendelson & Campbell, 1994)", "TaxonKey is Exerodonta melanomma (Taylor, 1940)", "TaxonKey is Megastomatohyla mixe (Duellman, 1965)", "TaxonKey is Exerodonta juanitae (Snyder, 1972)", "TaxonKey is Hyla plicata Brocchi, 1877", "TaxonKey is Exerodonta pinorum (Taylor, 1937)", "TaxonKey is Exerodonta smaragdina (Taylor, 1940)" ] } The dataset includes 11847 records from 77 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0005883-150615163101818/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences